Consistent sex ratio bias of individual female dragon lizards. - Uller, T; Mott, B; Odierna, G; Olsson, M (2006)
Sex ratio evolution relies on genetic variation in either the phenotypic traits that influence sex ratios or sex-determining mechanisms. However, consistent variation among females in offspring sex ratio is rarely investigated. Here, we show that female painted dragons (Ctenophorus pictus) have highly repeatable sex ratios among clutches within years. A consistent effect of female identity could represent stable phenotypic differences among females or genetic variation in sex-determining mechanisms. Sex ratios were not correlated with female size, body condition or coloration. Furthermore, sex ratios were not influenced by incubation temperature. However, the variation among females resulted in female-biased mean population sex ratios at hatching both within and among years.